A Prototyping Virtual Socket System-On-Platform Architecture with a Novel ACQPPS Motion Estimator for H.264 Video Encoding Applications. (22nd September 2009) - Qiu, Yifeng; Badawy, Wael
Abstract : H.264 delivers the streaming video in high quality for various applications. The coding tools involved in H.264, however, make its video codec implementation very complicated, raising the need for algorithm optimization, and hardware acceleration. In this paper, a novel adaptive crossed quarter polar pattern search (ACQPPS) algorithm is proposed to realize an enhanced inter prediction for H.264. Moreover, an efficient prototyping system-on-platform architecture is also presented, which can be utilized for a realization of H.264 baseline profile encoder with the support of integrated ACQPPS motion estimator and related video IP accelerators. The implementation results show that ACQPPS motion estimator can achieve very high estimated image quality comparable to that from the full search method, in terms of peak signal-to-noise ratio (PSNR), while keeping the complexity at an extremely low level. With the integrated IP accelerators and optimized techniques, the proposed system-on-platform architecture sufficiently supports the H.264 real-time encoding with the low cost.